2019
DOI: 10.3390/c5030042
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Catalytic CNTs Growth in 400–650 °C Range: Explaining Volcano Shape Arrhenius Plot and Catalytic Synergism Using both Pt (or Pd) and Ni, Co or Fe

Abstract: The Arrhenius plot of catalytic carbon formation from olefins on Ni, Co, and Fe has a volcano shape in the range 400–550 °C with reaction orders 0 (at lower T: Below ~500 °C) and one (at higher T: Above ~500 °C) at each side of the maximum rate. The reaction follows a catalytic route with surface decomposition of the gas (olefin) on the catalyst nanoparticle, followed by the bulk diffusion of carbon atoms and carbon nanotube growth on the opposite side. At the higher temperature region (500–550 °C), the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The Arrhenius plots shown in Figure 1 evidence the change of rate determining step at about 700 °C. Explanation of that change has been recently reminded [ 51 ]. Every point in the Arrhenius plot is a register of a steady-state deposition rate experiment (kinetic linearity observed) [ 5 ], that is, a full steady state C formation experiment, lasting 2 or 3 h. The volcano shape maximum with Fe and steel occurs at higher temperatures than with Ni and Co.…”
Section: Kinetic Routes/mechanisms Of Cnts and Graphene Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arrhenius plots shown in Figure 1 evidence the change of rate determining step at about 700 °C. Explanation of that change has been recently reminded [ 51 ]. Every point in the Arrhenius plot is a register of a steady-state deposition rate experiment (kinetic linearity observed) [ 5 ], that is, a full steady state C formation experiment, lasting 2 or 3 h. The volcano shape maximum with Fe and steel occurs at higher temperatures than with Ni and Co.…”
Section: Kinetic Routes/mechanisms Of Cnts and Graphene Formationmentioning
confidence: 99%
“…The two sides of the volcano correspond to the same mechanism (Route I, Catalytic), but with a change of the rate-determining step from C bulk diffusion to surface reaction decomposition of the gas reactant (C 2 H 2 and low olefins, only). The other C formation gases only operate at higher temperatures by impingement of pyrolytic formed carbon (C 2 ,C 3 …), C atoms entering the bulk of the catalyst and growing catalytically on the other side of the nano-particle [ 51 ]. In the studies of Puretzky et al, the reason a volcano shape was observed in the plot of the variation of the growth rates as a function of temperature was attributed to acetylene flow rates [ 57 ].…”
Section: Kinetic Routes/mechanisms Of Cnts and Graphene Formationmentioning
confidence: 99%
“…In a recent review, three kinetic routes for chemical vapor deposition (CVD) were distinguished: catalytic, hybrid and pyrolytic [24]. The volcano shape Arrhenius plot, found at lower temperatures (400-650 • C), has been clarified, based on a survey of kinetic studies [25].…”
Section: Kinetic Routes Alternative Growth Mechanismsmentioning
confidence: 99%
“…Those results were always inserted in an Arrhenius plot scale to evidence the activation energy. The Arrhenius plots are based in successive insertion of points corresponding to many steady-state rates of carbon formation measurements using a vacuum microbalance, as shown in Figure 3 and also in a recent short review [24]. A simplified scheme of the alternative routes was proposed by Figueiredo and co-workers [27] and used by Ashik et al [21].…”
Section: Kinetic Routes Alternative Growth Mechanismsmentioning
confidence: 99%
“…"Optimizing industrial production of carbon nanotubes is an important objective nowadays. Knowing the mechanisms operating helps to control properties, optimize production and reduce costs more easily" [76].…”
Section: Bamboo-like Hexagonal Boron Nitride (H-bn) Nanotubes and Thimentioning
confidence: 99%